The protein kinase Cmk2 negatively regulates the calcium/calcineurin signalling pathway and expression of calcium pump genes PMR1 and PMC1 in budding yeast - Huihui Xu; Tianshu Fang; Hongbo Yan; Linghuo Jiang (Cell Communication and Signaling, 2019)
Abstract Through a genome-wide screen we have identified calcium-tolerant deletion mutants for five genes in the budding yeast Saccharomyces cerevisiae. In addition to CNB1 and RCN1 that are known to play a role in the calcium signalling pathway, the protein kinase gene CMK2, the sphingolipid homeostasis-related gene ORM2 and the gene SIF2 encoding the WD40 repeat-containing subunit of Set3C histone deacetylase complex are involved in the calcium sensitivity of yeast cells to extracellular calcium. Cmk2 and the transcription factor Crz1 have opposite functions in the response of yeast cells to calcium stress. Deletion of CMK2 elevates the level of calcium/calcineurin signalling and increases the expression level of PMR1 and PMC1, which is dependent on Crz1. Effects of Cmk2 on calcium sensitivity and calcium/calcineurin signalling are dependent on its kinase activity. Therefore, Cmk2 is a negative feedback controller of the calcium/calcineurin signalling pathway. Furthermore, the cmk2 crz1 double deletion mutant is more resistant than the crz1 deletion mutant, suggesting that Cmk2 has an additional Crz1-independent role in promoting calcium tolerance.